Drought Facilitates Species Invasions in an Urban Stream: Results From a Long-Term Study of Tropical Island Fish Assemblage Structure - Ramírez, Alonso; Gutiérrez-Fonseca, Pablo E.; Kelly, Sean P.; Engman, Augustin C.; Wagner, Karleen; Rosas, Keysa G.; Rodríguez, Natalia (Frontiers in Ecology and Evolution, 2018)
The natural flow regime is a key regulator of the dynamics of stream communities and ecosystem processes. Native fish assemblages are evolutionarily adapted to their local flow regime. In the Caribbean, streams are vulnerable to changes in climate that will alter their flow regimes. We assessed long-term patterns in fish assemblages (2008-2016) in an urban stream in San Juan, Puerto Rico. We hypothesized that drought periods would result in negative effects on native fish species and positive effects on introduced species. Fish assemblages were sampled annually from 2008 to 2016 by backpack electrofishing, with additional sampling during 2015, which was a drought year. Cumulative dry season discharge was consistently over 300 m3/s from 2008 to 2013, except from 2014 to 2016 when it dropped below 170 m3/s. Thirteen species were found, including most native species reported for Puerto Rico and introduced species (e.g., Cichlids, Poeciliids, and Loracariids). Native species were dominant in abundance during most years, except during drought and post-drought sampling events when introduced species became dominant. Introduced species increased in richness with time from less than two species between 2008 and 2013 to seven in 2015. The increase in introduced species was mostly attributed to the appearance of several species of cichlids towards the end of the study. Cluster analysis divided the data set in two groups: drought and non-drought sampling events. Introduced cichlids and the native A. monticola accounted for more than 60% of assemblage dissimilarity. Fish assemblage abundance and richness were negatively related to several components of stream hydrology (e.g., cumulative daily stream discharge, the number of major floods). A significant change in size over time was found for the native A. monticola, which decreased in size during the drought period. Overall, our study documents drought-facilitated invasions by several aggressive and highly ecologically competitive species, highlights the importance of the natural flow regime as a source of environmental resilience to invasions in tropical island streams, and provides an example of how climate change has and will likely continue to alter Caribbean stream fish assemblages.